Positive correlation between post-cessation weight concerns and intentions to quit smoking in Chinese male smokers: A cross-sectional study - Yunyun He+; Chenzhang Diao+; Lianyi Wen; Qing Zhou; Lilong Pang; Lingling Song; Yiwen Yang; Ting Chen (Tobacco Induced Diseases)
Introduction Concerns about post-cessation weight gain might influence the attempts to quit smoking. The knowledge about post-cessation weight gain, the post-cessation weight concerns, and their relationship to smoking quit intention have not been thoroughly studied in the Chinese population.